The new screening program to prevent cervical cancer using HPV DNA: getting the balance right in maintaining quality. (11th September 2018) - Garland, Suzanne M; Dimech, Wayne; Collignon, Peter; ,; Cooley, Louise; Nimmo, Graeme R; Smith, David W; Baird, Rob; Rawlinson, William; Costa, Anna‐Maria; Higgins, Geoff
Abstract: Along with the reduction in human papillomavirus (HPV) infection and cervical abnormalities as a result of the successful HPV vaccination program, Australia is adopting a new screening strategy. This involves a new paradigm moving from cervical cytological screening to molecular nucleic acid technology (NAT), using HPV DNA assays as primary screening methodology for cervical cancer prevention. These assays must strike a balance between sufficient clinical sensitivity to detect or predict high‐grade cervical intraepithelial lesions, the precursor to cervical cancer, without being too sensitive and detecting transient infection not destined for disease. Ensuring the highest quality HPV NAT is thus a priority in order to reduce the possibility of falsely negative screens and manage the risk associated with false positive HPV NAT test results. How to do this needs informed discussion and on‐going refinement of the screening algorithm. This is of relevance as more countries move to more sensitive HPV NAT tests for secondary prevention of cervical cancer and as more HPV assays become available.